Development of a Career Stress Scale for Hospital Nurses: Implications for Workplace Counseling. Issue 4 (4th December 2017) - Yang, Peter
Abstract : The author performed 3 studies to investigate the construct validation and applicability of a Career Stress Scale for hospital nurses. After conducting an exploratory factor analysis on a sample of 141 nurses in the 1st study, the author examined divergent and convergent validity in the 2nd study, and performed a confirmatory factor analysis to test the hypothesized model on a sample of 284 teaching hospital nurses. The final study aimed to expand the findings, and the author used multigroup structural equation modeling to examine the measurement invariance of the Career Stress Scale for a district hospital, in a sample of 166 nurses. Recommendations for future studies and workplace counseling are discussed.